Tourism Development in the Lake Toba Region to Achieve the Sustainability of Local Wisdom-Based Tourism Villages in Parsingguran II Village - Sinulingga, Samerdanta; Sibarani, Halasan Sugianto (International Conference on Sciences Development and Technology, 2022)
Parsingguran II Village has tourism potential which is rich in natural beauty and unique local wisdom. However, to optimize this potential, it is necessary to develop and implement a pilot village tourism model based on local wisdom. This study aims to formulate a pioneering model of a tourism village based on local wisdom in Parsingguran II Village. The research method used is qualitative research with a case study approach. Data was obtained through observation, interviews, and documentation. Research participants included local communities, traditional leaders, village government, and other related parties. The results of the study show that Parsingguran II Village has a variety of local wisdom that can be used as a tourist attraction. The existence of beautiful nature, cultural diversity, and traditional craft skills are the main potentials that can be utilized. In addition, the participation and involvement of local communities in the development and management of tourism is very important. The proposed tourism village pilot model includes several important steps. First, identifying tourism potential based on local wisdom in Parsingguran II Village. Second, the development of adequate infrastructure to support tourism activities. Third, community involvement in decision-making and tourism management. Fourth, effective tourism promotion and marketing to attract tourists. The implementation of this tourism village pilot model is expected to provide social and economic benefits for the local community of Parsingguran II Village. In addition, by prioritizing local wisdom,